Fine root dynamics and its relationship with soil fertility in tropical rainforests of Chocó - Quinto, Harley; Caicedo, Haylin; Perez, May Thelis; Moreno, Flavio (Revista de Biología Tropical, 2016)
The fine roots play an important role in the acquisition of water and minerals from the soil, the global carbon balance and mitigation of climate change. The dynamics (productivity and turnover) of fine roots is essential for nutrient cycling and carbon balance of forest ecosystems. The availability of soil water and nutrients has significantly determined the productivity and turnover of fine roots. It has been hypothesized that fine roots dynamics increases with the availability of soil resources in tropical forest ecosystems. To test this hypothesis in tropical rainforests of Chocó (ecosystems with the highest rainfall in the world), five one-ha permanent plots were established in the localities of Opogodó and Pacurita, where the productivity and turnover of fine roots were measured at 0-10 cm and 10-20 cm depth. The measurement of the fine root production was realized by the Ingrowth core method. The fine root turnover was measured like fine roots production divided mean annual biomass. In addition, soil fertility parameters (pH, nutrients, and texture) were measured and their association with productivity and turnover of fine roots was evaluated. It was found that the sites had nutrient-poor soils. The localities also differ in soil; Opogodó has sandy soils and flat topography, and Pacurita has clay soils, rich in aluminum and mountainous topography. In Opogodó fine root production was 6.50 ± 2.62 t/ha.yr (mean ± SD). In Pacurita, fine root production was 3.61 ± 0.88 t/ha.yr. Also in Opogodó, the fine root turnover was higher than in Pacurita (1.17 /y and 0.62 /y, respectively). Fine root turnover and production in the upper soil layers (10 cm upper soil) was considerably higher. Productivity and turnover of fine roots showed positive correlation with pH and contents of organic matter, total N, K, Mg, and sand; whereas correlations were negative with ECEC and contents of Al, silt, and clay. The percentage of sand was the parameter that best explained the variations of fine root production. The fine root turnover was negatively explained by soil Al availability. Results suggested the increase of fine root dynamics with soil fertility at a local scale, which also indicates that under the oligotrophic conditions of soils in tropical rainforests, fine roots tend to proliferate rapidly in small patches of soil rich in sand and nutrients.